Effects of photovoltaic power station construction on terrestrial ecosystems: A meta-analysis - Zhang, Yong; Tian, Zhengqing; Liu, Benli; Chen, Shengyun; Wu, Jihua (Frontiers in Ecology and Evolution, 2023)
The rapid increase in construction of solar photovoltaic power stations (SPPs) has motivated ecologists to understand how these stations affect terrestrial ecosystems. Comparing study sites, effects are often not consistent, and a more systematic assessment of this topic remains lacking. Here, we evaluated the effects of SPP construction on carbon emissions, edaphic variables, microclimatic factors and vegetation characteristics in a meta-analysis. We employed log response ratios (as effect sizes) to assess how control plots differed from those beneath solar photovoltaic panels. We found that SPP construction decreased the local air temperature and photosynthetically active radiation, while increasing air humidity, especially in grasslands. Furthermore, plant aboveground biomass and vegetation cover were also enhanced by SPP construction in grassland ecosystems. In farmland ecosystems, photovoltaic panel installation increased plant aboveground biomass, soil available phosphorus and soil pH, while reducing CO2 flux, plant species richness and vegetation cover in woodlands. Thus, while SPP construction had profound ecological impacts in terrestrial ecosystems, the direction and strength of these effects was largely dependent on ecosystem type. Most studies of SPP construction to date have focused on local microclimatic and plant diversity effects, but few studies have examined effects on ecosystem functions and services. Future assessments are needed of both the benefits and disbenefits of SPP construction across different ecosystems, to improve SPP site selection and adaptive management.